2012
DOI: 10.1017/s0007114512001225
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acid fromLactobacillus rhamnosus GGas an oral photoprotective agent against UV-induced carcinogenesis

Abstract: Probiotics are live micro-organisms that when administered in adequate amounts confer a health benefit on the host. Cell surface molecules of these micro-organisms are being studied in relation to their ability to interact with the host. The cell wall of lactobacilli possesses lipoteichoic acids (LTA) which are molecules with immunomodulatory properties. UV radiation (UVR) has been proposed as the main cause of skin cancer because of its mutagenic and immunosuppressive effects. Photoprotection with some nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…For examples, The oral administration of purified LTA from Lactobacillus rhamnosus GG can modulate the immune-suppressive effect of UV and skin tumor development in female Crl:SKH-1-hrBR mice (Weill et al, 2013). Commensal bacteria lipoteichoic acid increases skin mast cell antimicrobial activity against vaccinia viruses (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examples, The oral administration of purified LTA from Lactobacillus rhamnosus GG can modulate the immune-suppressive effect of UV and skin tumor development in female Crl:SKH-1-hrBR mice (Weill et al, 2013). Commensal bacteria lipoteichoic acid increases skin mast cell antimicrobial activity against vaccinia viruses (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LTA is known to increase the activity of MMP-9, play an active role in otitis media, inhibit melanogenesis in B16F10 mouse melanoma cells, protect UV-induced carcinogenesis and increases skin mast cell antimicrobial activity against vaccinia viruses (Park et al, 2012;Wang et al, 2012;Weill et al, 2013;Kim et al, 2015). In addition, tolerance using LTA has been used to introduce to protect against pro-inflammation and other diseases (Kim et al, 2008b;Ellingsen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that this effect could be occurring in a non-antigen-specific fashion [7]. Similarly, in our laboratory, we have proven that LTA from L. rhamnosus GG administered to chronically UV-irradiated animals increases CD4+ and CD8+ T-cells, as well as it increases IFN-γ secretion in SLN [54]. …”
Section: Possible Mechanisms Involved In the Skin Effects Of Oral mentioning
confidence: 76%
“…This is the first report of a mixed treatment of oral probiotics and regular chemotherapy, in an effort to improve the efficacy of the latter [7]. Furthermore, in our laboratory, we have demonstrated that oral administration of purified lipoteichoic acid (LTA) from L. rhamnosus GG retards and reduces UV-induced skin squamous cell carcinomas, in a mouse model of chronic UV irradiation [54]. …”
Section: Probiotics and Cancermentioning
confidence: 99%
“…Almost a century ago, Findlay described the ability of UV light to induce skin cancer in albino mice chronically exposed to a quartz mercury‐vapour lamp . Plenty of experimental conditions were analysed since then in animal models; we would like to highlight the following concepts: (i) chronic exposure to UV light leads to non‐melanoma skin cancer development; this observation is valid when animals were exposed to UVr doses above the minimal erythemal dose (MED, a dose that promotes visible damage by itself) but also for sub‐erythemal doses (around half the MED) . (ii) Acute exposure to UVr promotes a deficient adaptive immune response; this well‐known immunosuppressive effect has been demonstrated by exposing animals to a single UV exposure (above MED) as well as to several exposures to low UV doses (around half the MED and applied on a few consecutive days).…”
Section: Introductionmentioning
confidence: 99%